2002
DOI: 10.1007/s11357-002-0010-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived Ames dwarf mice: Oxidative damage to mitochondrial DNA in heart and brain

Abstract: The single gene mutation of Ames dwarf mice increases their maximum longevity by around 40% but the mechanism(s) responsible for this effect remain to be identified. This animal model thus offers a unique possibility of testing the mitochondrial theory of aging. In this investigation, oxidative damage to mitochondrial DNA (mtDNA) was measured for the first time in dwarf and wild type mice of both sexes. In the brain, 8-oxo,7,8-dihydro-2'-deoxyguanosine (8-oxodG) in mtDNA was significantly lower in dwarfs than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…This indicates that the effects of these hormones are complex and can include both increases and decreases in oxidative stress. These changes would be concordant with the proaging (Brown-Borg et al 1996;Coshigano et al 2000;Clancy et al 2001;Flurkey et al 2001;Kenyon 2001;Sanz et al 2002;Bluher et al 2003;Holzenberg et al 2003) and antiaging (Papadakis et al 1996;Markowska et al 1998;Lichtenwalner et al 2001;Sonntag et al 2001;French et al 2002;Castillo et al 2003) roles described for these hormones and insulin-like signalling in different animal models. However, our study was performed in young animals.…”
Section: Discussionsupporting
confidence: 83%
“…This indicates that the effects of these hormones are complex and can include both increases and decreases in oxidative stress. These changes would be concordant with the proaging (Brown-Borg et al 1996;Coshigano et al 2000;Clancy et al 2001;Flurkey et al 2001;Kenyon 2001;Sanz et al 2002;Bluher et al 2003;Holzenberg et al 2003) and antiaging (Papadakis et al 1996;Markowska et al 1998;Lichtenwalner et al 2001;Sonntag et al 2001;French et al 2002;Castillo et al 2003) roles described for these hormones and insulin-like signalling in different animal models. However, our study was performed in young animals.…”
Section: Discussionsupporting
confidence: 83%
“…A recent report by Choksi et al (2007) showed that Ames mice have lower levels of isoprostanes in both serum and liver at multiple ages, suggestive of lower oxidative stress. The reduced ROS and elevated antioxidative capacity of dwarf mice leads to lower nuclear DNA, mitochondrial DNA, and protein oxidative damage in several tissues (Brown-Borg et al, 2001a,b; Sanz et al, 2002). Functionally, Ames mice out-survive their GH sufficient counterparts following paraquat administration (systemic oxidative stressor; Bartke et al, 2000).…”
Section: Gh and Stress Resistancementioning
confidence: 99%
“…8-oxodG in mtDNA from brain tissue was 32% lower in male and 36% lower in female Ames dwarf mice; 8-oxodG in mtDNA from heart tissue was 30% lower in male Ames dwarf mice, while there were not differences among females [57] . Snell dwarf mice show evidence of reduced oxidative stress in comparison to their wild-type counterparts [2] .…”
Section: Oxidative Stressmentioning
confidence: 75%